High performance, electroforming-free, thin film memristors using ionic Na0.5Bi0.5TiO3. Issue 13 (18th March 2021) - Yun, Chao; Webb, Matthew; Li, Weiwei; Wu, Rui; Xiao, Ming; Hellenbrand, Markus; Kursumovic, Ahmed; Dou, Hongyi; Gao, Xingyao; Dhole, Samyak; Zhang, Di; Chen, Aiping; et al.
Abstract : Interfacial resistive switching and composition-tunable R LRS are realized in ionically conducting Na0.5 Bi0.5 TiO3 thin films, allowing optimised ON/OFF ratio (>10 4 ) to be achieved with low growth temperature (600 °C) and low thickness (<20 nm). Abstract : Here, in ionically conducting Na0.5 Bi0.5 TiO3 (NBT), we explore the link between growth parameters, stoichiometry and resistive switching behavior and show NBT to be a highly tunable system. We show that the combination of oxygen ionic vacancies and low-level electronic conduction is important for controlling Schottky barrier interfacial switching. We achieve a large ON/OFF ratio for high resistance/low resistance ( R HRS / R LRS ), enabled by an almost constant R HRS of ∼10 9 Ω, and composition-tunable R LRS value modulated by growth temperature. R HRS / R LRS ratios of up to 10 4 and pronounced resistive switching at low voltages (SET voltage of <1.2 V without high-voltage electroforming), strong endurance (no change in resistance states after several 10 3 cycles), uniformity, stable switching and fast switching speed are achieved. Of particular interest is that the best performance is achieved at the lowest growth temperature studied (600 °C), which is opposite to the case of most other perovskite oxides for memristors, where higher growth temperatures are required for optimum performance. This is understood based on the oxygen vacancy control of interfacial switching in NBT, whereas a range of other mechanisms (including filamentary switching) occur in other perovskites. The study of NBT has enabled us to determine key parameters for achieving high performance memristors.